Pengaruh Edukasi Gizi Terhadap Sisa Makan Pasien Dengan Diet Makanan Biasa - Herawati, Maulany Retno; Subandriani, Dyah Nur; Hunandar, Cahyo (Poltekkes Kemenkes Semarang, 2014)
Background : Patient acceptability of the food served can be seen from the leftovers. Data leftovers are generally used to evaluate the effectiveness of nutrition education programs, activities and food service, as well as the adequacy of food consumption on a group or individualObjective : Determine the effect of nutrition education on eating the rest of the patients with usual diet in the class III Inpatient Hospital Kalidjaga Sunan DemakMethod : This research is penilitian Quasi- Experiment with design Nonequivalen control group design. independent variable is nutrition education, while the dependent variable is the leftovers. The study subjects who used a number of 48 people were divided into treatment group and control group 24 persons 24 persons. Bivariate analysis used were paired t - test and independent t - test. The rest of the food was measured by the method comstok patients to determine the effect of education on food waste.Results : The rest of the patients before and after food nutrition education for patients (control group) by an average of 32.17 and 20:25 . The rest of the patients before and after food without nutrition education hospitalized patients (group treatments) by an average of 22:29 and 12.96.Conclusion : Differences leftovers patients at initial measurement (before education) and the final measurement (after education) in the treatment group gained an average of 9,333. Differences leftovers patients at the end of the initial measurements and measurements obtained in the absence of the provision of education on average 11, 917. Differences leftovers patients in the treatment group and the control group by 7,292. There are differences in the group of patients leftovers with nutrition education and nutrition education group in hospitals without Kalidjaga Sunan Demak years 2014secara significant with p - value: 0.000.